The calling ebook The inn at eagle hill series, book 2. - Fisher, Suzanne Woods (Inn at Eagle Hill, 2014)
Bethany Schrock's love life has derailed, her faith hangs by a thread, and a family secret holds her in its grip. Can the handsome Jimmy Fisher help her find the answers she needs—and the love she craves?